Problems of Poverty and Social Exclusion - Vidanović, Vojin (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Beside unemployement, poverty is one of the most severe social problems influencing all spheres of personal and social position of individuals as well as of social groups. In recent years, special care has been given to the realisation of poverty alleviation strategies that, besides economic stimulation programmes, include special programmes of social inclusion. The goal is to aid individuals in social risks as well as to marginalised groups in self-employment and active influence on change of their social position, which includes social enterprising.